Modern drawing : a contemporary exploration of drawing and illustration - Ward, Chelsea (Walter Foster Publishing, 2018)
Modern Drawing isn't a dry instruction manual; it's a contemporary guide filled with instruction, encouragement, and loads of helpful tips. Learn how to use basic drawing principles and techniques to create fresh, expressive pieces of art. With Modern Drawing, you'll enjoy a dynamic, easy-to-follow exploration of drawing media and tools as you work through creative exercises and projects. You'll also learn how to "see" a subject and render a personal yet modern interpretation of their observations on paper